PEMANFAATAN WAKTU LUANG NELAYAN DI LUAR PEKERJAANNYA KE LAUT - Mariyam Musawa; M. Suryaningsih; Aufarul Marom (JURNAL ILMU SOSIAL, 2007)
In order side of his work in fishing and sailing on the sea, the fisherman has a lot of time that useless effectively. There are many hours that can be used for increasing his income or earning. His unoccupied time generally used for selling “bakso”, as a driver of “ojek” small trading, boot rental for fishing as hobbies etc. Using this unoccupied time ussally caused of the grand wave on the sea, so, it’s dangerous for him to sail. Other fisherman has skill to make something got from the sea has value added, like to make “terasi”. The fisherman got the information from the government how to develop his skill to increasing his income.